2019
DOI: 10.1097/md.0000000000014942
|View full text |Cite
|
Sign up to set email alerts
|

Association between NAT2 polymorphisms and acute leukemia risk

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…To our knowledge, no previous studies have explored the relationship between NAT2 genotypes and these environmental factors in ALL. However, differential contribution of single NAT2 SNPs to the risk of ALL has been observed recently by Zhu et al, who performed a meta-analysis including 1,522 acute leukemia patients and 2,688 controls (11).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…To our knowledge, no previous studies have explored the relationship between NAT2 genotypes and these environmental factors in ALL. However, differential contribution of single NAT2 SNPs to the risk of ALL has been observed recently by Zhu et al, who performed a meta-analysis including 1,522 acute leukemia patients and 2,688 controls (11).…”
Section: Discussionmentioning
confidence: 96%
“…Since ALL is considered a multifactorial disease where xenobiotics could be important factors that contribute to its pathogenesis, and that NQO1, CYP2E1 , and NAT2 are enzymes involved in the metabolism of xenobiotics (including benzene, cigarette smoking, chemotherapy agents, and alcohol drinking), which increase the risk to develop diverse human diseases ( 2 , 11 , 19 ), we used a MDR approach to identify combinations between genetic and environmental factors associated with ALL ( 29 ). Our data showed that the NAT2 _rs1799929- NAT2 _rs1208-ACMBP-MCMBP-PSFBC interact to increase the risk of ALL before pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a Brazilian study demonstrated that NAT2 * 14, NAT2 * 5A, and NAT2 * 5C are correlated with an increased susceptibility to ALL in a Brazilian population [27,28]. Recently, a research group reviewed the published literature on the correlation between NAT2 genetic variants and susceptibility to acute leukemia and it was reported that rs1801280 (341T>C (NAT2 * 5)) contributes to the disease [29]. Having a high percentage of this NAT2 * 5A polymor-phism (23%) among Al-Ahsa community may make them vulnerable to acute leukemia, taking into account that the Eastern region is the second in the prevalence of leukemia in the Kingdom after Riyadh [30].…”
mentioning
confidence: 99%